Adult time-mortality response and changes in reproductive attributes in Callosobruchus maculatus (Fab.) following UV irradiation (Journal of Life and Earth Science, 2011)
Using 254nm UV radiations of exposure periods from 2 to 16 min against adults. Time mortality response of the cowpea weevil, Callosobruchus maculatus (Fab.) (Coleoptera: Bruchidae), adults and alterations in vital reproductive attributes as fecundity, immature duration, adult emergence and adult longevity of the beetles from parental through F1 generation have been estimated. Time mortality response of the adults of the cowpea weevil Callosobruchus maculatus (Fab.) (Coleoptera: Bruchidae), and alternations in vital reproductive attributes is fecundity, immature duration, adult emergence and longevity from parental through F1 generation using 254nm UV radiations of response periods from 2-16min have been estimated. Results show that an exposure time to kill 50% of the adults is around 20 min (LT50 = 19.99min), and irradiation significantly reduced egg-laying (P